Wettability characterization of 3D printed polymer membranes with candle soot coating - Mohd Zini, Nurul Hilwa; Arbain, Nurul Afiqah; Shikh Anuar, Fadhilah; Abdollah, Mohd Fadzli; Rosley, Mohd Idain Fahmy (Malaysian Tribology Society (Mytribos), 2024)
Wettability of a membrane plays an important role in enhancing separation efficiency and it can be assessed by determining the contact angle of liquid on a surface. In recent years, there is a lot of interest in developing hydrophobic surfaces for oil-water separation. However, implementation of candle soot on 3D printed polymer membranes has not fully explored. This study aimed to characterize the wettability of 3D printed polymer membranes with candle soot coating to improve the oil-water separation efficiency. Polyamide-based membranes were fabricated using Selective Laser Sintering (SLS) and modified with paraffin candle soot. Coated and non-coated membranes for both top and bottom surface morphology were monitored and the values of surface roughness and contact angle were recorded. Coated membranes recorded 16% and 29% higher surface roughness values for the top and bottom surfaces compared to the non-coated membranes; top and bottom surfaces of coated membranes also recorded increases in the contact angle values of 6.6% and 11.25%, respectively. Membranes’ contact angle was affected by the roughness due to the coated carbon nanoparticle from the soot and printing technologies. It can be concluded, 3D printed polymer membrane with candle soot coating is an effective way in fabricating a hydrophobic membrane.